Hindutva, the emergence of the right - Lele, Jayant (Madras : Earthworm Books ; New Delhi : Distributed by Affiliated East-West Press, 1995)
Articles on religiopolitical scene of contemporary Maharashtra State, India.
Keywords: Religion and politics -- India -- Maharashtra; Secularism -- India -- Maharashtra; Maharashtra (India) -- Politics and government